2002
DOI: 10.1080/20028091057565
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Multimedia Inorganic Arsenic Intake in the U.S. Population

Abstract: Arsenic is widely distributed in the environment by natural and human means. The potential for adverse health effects from inorganic arsenic depends on the level and route of exposure. To estimate potential health risks of inorganic arsenic, the apportionment of exposure among sources of inorganic arsenic is critical. In this study, daily inorganic arsenic intake of U.S. adults from food, water, and soil ingestion and from airborne particle inhalation was estimated. To account for variations in exposure across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 35 publications
3
65
2
1
Order By: Relevance
“…The daily exposure to inorganic As from eating rice cereal could be at least 0.0042 mg, modeled for a typical UK diet and based on inorganic As levels found in this survey. Meacher et al (2002) estimate that the 50th percentile intake of inorganic As from soil, air, drinking water and food for US men is 0.0040 mg, whilst for women it is 0.0031 mg. For US children, average exposure from dietary sources alone is estimated at 0.0032 mg (Yost et al, 2004). When exposure is considered on a body mass basis, though, children are more vulnerable than adults (Meharg et al, 2008a,b,c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The daily exposure to inorganic As from eating rice cereal could be at least 0.0042 mg, modeled for a typical UK diet and based on inorganic As levels found in this survey. Meacher et al (2002) estimate that the 50th percentile intake of inorganic As from soil, air, drinking water and food for US men is 0.0040 mg, whilst for women it is 0.0031 mg. For US children, average exposure from dietary sources alone is estimated at 0.0032 mg (Yost et al, 2004). When exposure is considered on a body mass basis, though, children are more vulnerable than adults (Meharg et al, 2008a,b,c).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have indicated that in countries not suffering from high levels of As in drinking water, rice is the major contributor to inorganic As in the human diet (Meacher et al, 2002;Meliker et al, 2006;Williams et al, 2007a). This is in part due to rice being particularly efficient at taking up As from soil (Williams et al, 2007b) and exacerbated in major rice growing regions of the world with elevated As in paddy soil caused by to anthropogenic contamination (Meharg 2004;Williams et al, 2005Williams et al, , 2006Williams et al, , 2007a.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic arsenic in different foods was estimated by averaging across the literature (Supplementary Table S2). Comparable methods have been employed (Meacher et al, 2002) and used in our previous reports (Slotnick et al, 2007). Frequency and quantity (serving size) was obtained from the FIQ.…”
Section: Calculation Of Exposure Metricsmentioning
confidence: 99%
“…The outcomes of this model evaluation provide valuable information with respect to expected confidence in applying MENTOR-4M to other areas as well as to identifying data gaps and relevant research needs for improving this confidence. For example, the modeling results of arsenic air exposure concentrations for the three counties were compared with the corresponding 1996 NATA calculations, while the multimedia/multipathway arsenic exposure estimates for one of the case studies (Franklin County, OH) were compared with the results of a nationalscale modeling study reported by Meacher et al (2002). To evaluate the intake/uptake estimates, the calculated biomarker (total arsenic in urine samples) levels for Franklin County, OH were compared with those measured in NHEXAS-V. An independent "pattern recognition" Classification and Regression Tree (CART) (Roy et al, 2003) analysis of the NHEXAS-V study data on arsenic was also performed.…”
Section: Model Evaluationmentioning
confidence: 99%
“…Estimates-The MENTOR-4M estimates of total inorganic arsenic intakes for adult men and women of Franklin County, OH were compared with the corresponding estimates of a nationwide study (Meacher et al, 2002). The cumulative distributions of intake values estimated in the two studies were compared to assess the agreement across different percentiles of the population.…”
Section: Comparisons Of Total Inorganic Arsenic Intake Predictions Wimentioning
confidence: 99%